Potencial de Traslado de los Individuos Arbóreos Emplazados en Espacio Público por Interferencia Directa con el Desarrollo de Proyectos de Obra e Infraestructura dentro del Perímetro Urbano de Bogotá D.C. (2023)
At present, construction and infrastructure projects are having a great boom within the city of Bogotá D.C, and with this there is also a concern in certain part of its inhabitants taking into account that, both in the stages of studies and designs As in the execution, a large number of tree specimens are affected, which are located within the limits of their area of ​​influence.